1976
DOI: 10.1152/jappl.1976.41.1.101
|View full text |Cite
|
Sign up to set email alerts
|

A new method to determine frequency characteristics of the respiratory system

Abstract: A technique is described allowing one to determine simultaneously the resistance and reactance of the total respiratory system for various frequencies. During spontaneous breathing, regularly recurring impulses are produced at the mouth by means of a loud speaker. A Fourier analysis of the mouth pressure and flow signals yields mean resistance and reactance values, over 16 s, for all harmonics of 2 Hz up to 30 Hz. The values are in good agreement with those obtained in the absence of breathing and those determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
0
8

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(128 citation statements)
references
References 7 publications
5
115
0
8
Order By: Relevance
“…The changes in R and 0Zrs0 with condition were most pronounced at 1.5 Hz and had disappeared at 5 Hz. In humans, the larger change in R at low vs. high frequencies has been demonstrated after bronchial challenge (19), in asthmatic vs. normal humans (9,13), and in asthmatic subjects after bronchodilation (20). The definitions of ''high'' and ''low'' frequencies depend on the size of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in R and 0Zrs0 with condition were most pronounced at 1.5 Hz and had disappeared at 5 Hz. In humans, the larger change in R at low vs. high frequencies has been demonstrated after bronchial challenge (19), in asthmatic vs. normal humans (9,13), and in asthmatic subjects after bronchodilation (20). The definitions of ''high'' and ''low'' frequencies depend on the size of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…The difference observed between our group 1 and 2 patients is not due to a particular observation tilting the mean in small groups. In particular, there is no The negative slope of resistance at low frequencies associated with a low reactance is not specific to pulmonary vascular congestion and has been described in obstructive lung diseases 14,24,29,30 Mechanical inhomogeneities of the lung and upper airways have usually been invoked to interpret this characteristic Zrs frequency dependence.11 14,30 According to the model described by Mead,3 an increase in slope of resistance vs frequency could be associated with an increase of resistance of the small airways. Numerous animal4'1 and human studies'8 have shown that pulmonary vascular congestion could induce small airways dysfunction, as shown by an increase in closing volume and peripheral airways resistance and by a decrease in dynamic compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory resistance Respiratory resistance (Rrs) was measured using a forced oscillation technique (Fuller et al, 1988;Landser et al, 1976). Three measurements of respiratory resistance were made before and a further measurement was made after single breaths of capsaicin at doses which caused less than two coughs.…”
Section: Challengesmentioning
confidence: 99%